Metabolismo fotossintético em genótipos de Jatropha curcas L. submetidos à deficiência hídrica - Silva, Leandro Dias (2016)
Jatropha curcas L. belonging to Euphorbiacae family, has received attention on the world stage for its applicability in environmental and economic sectors through the use of recovery programs of degraded areas such as hedge and biofuel production as an al